EDUKASI DAN PEMANFAATAN APLIKASI KEUANGAN ONLINE PADA PELAKU UKM SEBAGAI MEDIA UNTUK MENGELOLA KEUANGAN - Ardhiani Fadila (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This Service activities focus on educating and assisting SMEs in using digital-based financial applications to do business bookkeeping. SMEs in the Rancabungur area, Bogor are still not disciplined in doing business bookkeeping and recording manually. The method in this service activity is to conduct lectures on the importance of financial recording and assistance in using digital financial applications. The results of this activity can be seen from the enthusiasm of the participants in participating in the event and the motivation of SMEs in using digital financial applications. The results of this activity are expected to help SMEs to be more disciplined in carrying out financial records and be able to manage their business finances so that they are better and develop.